DETERMINING PURCHASE INTENTION IN HALAL PERSONAL CARE PRODUCT: STUDY ON MUSLIMAH MILLENNIAL GENERATION - Mahliza, Febrina; Prasetya, Prita (Jurnal Aplikasi Manajemen, 2021)
Currently, Indonesian citizens were mostly dominated by the millennial generation. The domination of this generation became a potential market for a halal product. However, millennials considered having less interest to dig more information about the "halalness" of products. Therefore, this study will focus on the millennial generation's halal personal care product purchase intention behavior. Method applied in this study was quantitative and the primary data taken from the millennial generation in Jakarta, which amounted to 104 respondents by purposive sampling. Further, Partial Least Square (PLS) was used as data analysis. The results study showed that halal personal care product's purchase intention was affected significantly by halal marketing and health reason. Halal awareness and certification did not significantly affect the millennial generation's purchase intention of halal personal care products.